2020
DOI: 10.1039/d0dt03314f
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of macrocyclic gadolinium-based MR contrast agents with Type I collagen. Equilibrium and kinetic studies

Abstract: The interactions of gadoterate meglumine, gadobutrol, gadoteridol and Gd(HB-DO3A) with bovine Type I collagen were investigated by ultrafiltration and dialysis. The affinity of the four agents to collagen is rather...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…Given that skin is a collagenrich tissue, this finding is consistent with findings from a recent in vitro study, which showed that gadoteridol accumulates to a lower degree in collagen than both gadoterate and gadobutrol. 23 Our findings for the skin are also consistent with those from a previous study of long-term Gd retention in the skin of rats, 24 which indicated considerably lower levels of retained Gd at early timepoints after a cumulative dose of 12.5 mmol/kg bodyweight (approximately 23 nmol Gd/g skin for gadoteridol at 3 days after the end of dosing compared to 50-60 nmol Gd/g skin for gadoterate and gadobutrol). Consistent with our findings, they showed that by day 35 after the end of dosing, the Gd levels in the skin were lower for gadoteridol (1 AE 1 nmol Gd/g), than for both gadoterate and gadobutrol (2 AE 1 nmol Gd/g).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Given that skin is a collagenrich tissue, this finding is consistent with findings from a recent in vitro study, which showed that gadoteridol accumulates to a lower degree in collagen than both gadoterate and gadobutrol. 23 Our findings for the skin are also consistent with those from a previous study of long-term Gd retention in the skin of rats, 24 which indicated considerably lower levels of retained Gd at early timepoints after a cumulative dose of 12.5 mmol/kg bodyweight (approximately 23 nmol Gd/g skin for gadoteridol at 3 days after the end of dosing compared to 50-60 nmol Gd/g skin for gadoterate and gadobutrol). Consistent with our findings, they showed that by day 35 after the end of dosing, the Gd levels in the skin were lower for gadoteridol (1 AE 1 nmol Gd/g), than for both gadoterate and gadobutrol (2 AE 1 nmol Gd/g).…”
Section: Discussionsupporting
confidence: 91%
“…This possibly reflects faster clearance of gadoteridol immediately after the GBCA administration phase. Given that skin is a collagen‐rich tissue, this finding is consistent with findings from a recent in vitro study, which showed that gadoteridol accumulates to a lower degree in collagen than both gadoterate and gadobutrol 23 . Our findings for the skin are also consistent with those from a previous study of long‐term Gd retention in the skin of rats, 24 which indicated considerably lower levels of retained Gd at early timepoints after a cumulative dose of 12.5 mmol/kg bodyweight (approximately 23 nmol Gd/g skin for gadoteridol at 3 days after the end of dosing compared to 50–60 nmol Gd/g skin for gadoterate and gadobutrol).…”
Section: Discussionsupporting
confidence: 90%
“…In common with other tissues evaluated, greater levels of retained Gd were noted with gadobutrol and gadoterate than with gadoteridol: at day 28 after treatment, the Gd content in peripheral nerves of SN rats treated with gadobutrol or gadoterate was 5.4 and 7.2 times higher, respectively, than in SN rats treated with gadoteridol. Considering that collagen is the main component of the extracellular matrix of peripheral nerves (comprising about 90% type I collagen [ 34 , 35 ]), our findings are consistent with those of a recent in vitro study, which showed that gadoteridol accumulates to a lower degree in collagen than both gadoterate and gadobutrol [ 36 ]. Our study also demonstrated that Gd content was higher in peripheral nerves than in both the cerebrum and cerebellum, particularly at day 28 after treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the observations may not represent a clinical scenario. The mechanism by which macrocyclic agents would be retained is unknown, although a recent report on interaction of macrocyclic GBCAs with collagen [ 86 ] suggests that binding of intact macrocyclic complexes to components of the extracellular matrix may account for the retention of intact macrocyclic GBCAs complexes. This study showed that all macrocyclic agents have similar affinity to collagen type I, but the maximum amount of collagen bound was slightly different: it decreased following the order of gadoterate meglumine > gadobutrol > gadoteridol.…”
Section: What Prediction Can We Make About Gadolinium Deposition? How Do Those Predictions Relate To Preclinical Results?mentioning
confidence: 99%